2009 ICSE Workshop on Cooperative and Human Aspects on Software Engineering 2009
DOI: 10.1109/chase.2009.5071401
|View full text |Cite
|
Sign up to set email alerts
|

Coordination in large-scale software teams

Abstract: Large-scale software development requires coordination within and between very large engineering teams which may be located in different buildings, on different company campuses, and in different time zones. From a survey answered by 775 Microsoft software engineers, we learned how work was coordinated within and between teams and how engineers felt about their success at these tasks. The respondents revealed that the most common objects of coordination are schedules and features, not code or interfaces, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 8 publications
0
36
0
Order By: Relevance
“…Paasivaara and Lassenius (2014) describe a very large-scale development initiative at Ericsson with 40 teams where four types of communities of practice (Wenger 1998) are used to coordinate teams. A survey on coordination in large-scale software teams found that respondents wished more effective and efficient communication, as well as the importance of good personal relationships for coordination (Begel et al 2009).…”
Section: Inter-team Coordinationmentioning
confidence: 99%
“…Paasivaara and Lassenius (2014) describe a very large-scale development initiative at Ericsson with 40 teams where four types of communities of practice (Wenger 1998) are used to coordinate teams. A survey on coordination in large-scale software teams found that respondents wished more effective and efficient communication, as well as the importance of good personal relationships for coordination (Begel et al 2009).…”
Section: Inter-team Coordinationmentioning
confidence: 99%
“…SentiStrength was originally developed for English and was optimised for short social web texts. We used 3 https:en.wikipedia.orgwikiMain Page 4 http:stackoverflow.com 5 Jira Issue Tracking System https://www.atlassian.com/software/jira 6 http://www.mpi-sws.org/cristian/Politeness.html 7 User's names are reported as <dev name a> for the sake of privacy. 8 http://sentistrength.wlv.ac.uk/ SentiStrenght to measure the sentiment of developers in issue comments (which often are short).…”
Section: B Sentimentmentioning
confidence: 99%
“…Similar to sports teams, human affectiveness in software engineering has a huge impact on the abilities of a software organization [3] [4], yet the need to collaborate with remote teams (both in closed and open source development) makes the situation even more challenging [5] [6]. The fact that people do not work physically in the same location not only makes coordination of tasks more difficult, it requires them to align with colleagues and interpret colleagues' feelings through emails, discussion boards (e.g., issue tracking systems) and conference calls.…”
Section: Introductionmentioning
confidence: 99%
“…From the discussion, the following conclusions follow on the coordination mechanisms: There is a growing number of studies on multiteam systems which we believe are relevant for practitioners and researchers in large-scale agile development. In particular it would be interesting for future research to further explore how human aspects influence coordination, following up on Begel et al [22] who found that creating and maintaining personal relationships was critical to good coordination. In the future, researchers should draw further on findings in the multiteam systems field to provide better advice on how these aspects can be fostered in development methods.…”
Section: Resultsmentioning
confidence: 99%
“…Begel et al [22] Unlike a traditional team, a multiteam system is too large and specialised to effectively employ direct mutual adjustment among each and every member of the system [25]. An empirical study by Marks and colleagues [26] points out that coordination 'involves synchronising the efforts of multiple teams in a joint endeavour to handle situational demands' [26, p. 965].…”
Section: Large-scale Agile Development: Studies and Practitioner Frammentioning
confidence: 99%